DAYLY DYNAMICS OF TRANSPIRATION INTENSITY OF SOYBEAN VARIETIES LEAVES (GLYCINE MAX. (L.) MERR.) IN CONDITIONS OF CHUI VALLEY (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The research work reflects some basic indicators of the water regime. Experimentalresearches were carried out on five varieties of soybean (Glycine max. (L.) Merr.), cultivated ongray soil of the Chui Valley (Kenesh village). During several seasons, research has been carriedout to study the water-holding capacity, the intensity of leaf transpiration and the water contentin the leaves of various soybean varieties. We determined the daily dynamics of transpirationintensity, its minimum and maximum values for domestic and foreign soybean varieties. It wasrevealed that the IT of leaves has a one- and two-peak curve, where its maximums were observedat 3 and 5 o’clock in the afternoon at air t +33-35°C. Based on the water content in the leaves andthe ability to retain water, the indicators of all samples remain in high concentrations for up tohalf a day. But with the increase in temperature and its decrease in the evening, a smooth declineis observed on the graph. Despite the arid climate of the northernmost region of the country,the conditions of the Chui Valley allow the cultivation of soybean varieties. The results obtaineddescribe their resistance to atmospheric and soil drought.
Keywords: Glycine max. (L.) Merr., different varieties, transpiration intensity, water content in leaves, weather conditions